Expression pattern and cellular localization of two critical non-nuclear progesterone receptors in the ovine corpus luteum during the estrous cycle and early pregnancy - Atli, Mehmet O.; Akbalik, Mehmet Erdem; Kose, Mehmet; Alak, Ilyas; Atli, Zehra; Hitit, Mustafa (Elsevier BV, 2022)
The study aimed to investigate the expression and cellular localization of two critical non-nuclear progesterone receptors, including membrane-associated-progesterone-receptor-component-1 (PGRMC1) and progestin and adipoQ receptor family member 7 (PAQR7) throughout the estrous cycle and early pregnancy in ovine corpus luteum (CL). Ewes were randomly grouped into cyclic (C, n = 4 per group) or pregnant (P, n = 4 per group) groups. Following slaughtering, the CL was obtained from both cyclic and pregnant ewes on days 12 (C12 and P12), 16 (C16 and P16), and 22 (C22 and P22). Western blotting and RT-qPCR were utilized to assess the expression levels of PGRMC1 and PAQR7, whereas immunohistochemistry was performed to determine the localization of PGRMC1 and PAQR7 in CL. Data were evaluated by one-way ANOVA, and the P < 0.05 was considered a significant difference. PGRMC1 was shown to be expressed in both small and large luteal cells and endothelial cells in CL, while PAQR7 expression was only found in small and large luteal cells. Compared to cycle days, pregnancy increased the expression of PGRMC1. PAQR7 did not differ during early pregnancy but reduced during the functional luteolysis stage (C16). mRNA and protein expression patterns for PGRMC1 and PAQR7 were similar on the studied days. This is the first study that demonstrates the expression and cellular localization of PGRMC1 and PAQR7 in ovine CL. We suggest that these receptors could execute a significant role in the ovine CL life span in both cyclic changes and the establishment of pregnancy.
Keywords: Sheep; Endothelial Cells; Estrous Cycle; Corpus Luteum; Pregnancy; Progesterone Membrane Receptors; Animals; Female; Receptors, Progesterone; Progesterone; Sheep, Domestic